Podnikatelský záměr - Božková, Lenka (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Diplomová práce je zaměřena na zpracování a předložení návrhu podnikatelského plánu nového střediska konkrétní obchodní společnosti. Předmětem činnosti zamýšleného střediska je výstavba a provozování školicího střediska pro vzdělávání vlastních zaměstnanců a obchodních partnerů v oblastech, ve kterých společnost podniká. Součástí práce je detailní analýza společnosti a její finanční pozice zaměřená na ověření připravenosti společnosti na zamýšlený projekt.

The Master thesis is focused on processing and presentation of the draft business plan for the new center of a specific company. The subject of the activity of proposed center is the construction and operation of training center for training their own employees and business partners in fields of business in which the company operates. The thesis contains detailed analysis of the company and its financial position focused on verifying readiness of the intended project.
Business Plan
Keywords: Analýza finanční pozice; investice; podnikatelský plán; školicí středisko.; Analysis of financial position; investments; business plan; training center.